Homo Machina: Italian Perspectives on Drone Warfare within International Humanitarian and Human Rights Law - Calzolari, Fabio; Phantanaboon, Wipa (Faculty of Law, Sriwijaya University, Indonesia, 2025)
The rise of unmanned aerial vehicles (UAVs) poses substantial challenges to international legal frameworks governing armed conflicts, particularly in balancing sovereignty and human rights. This paper examines the influence of military technology on jus ad bellum, focusing on territorial sovereignty under Article 2(4) of the UN Charter and self-defence under Article 51. It also evaluates compliance with jus in bello, or international humanitarian law (IHL), including the principles of distinction, proportionality, and necessity. Moreover, it documents the views of thirty Italians on UAVs through online qualitative interviews. The arguments are based on posthumanism, which helps define a new anthropological view that is decentralised and deconstructed. Precisely, the philosophy recognises the increasingly narrow differences between humans and non-humans, men and machines. Thematic Analysis drives the investigation of patterns within the data set, offering a flexible yet rigorous approach to personal insights. Outcomes reveal that UAVs enable many military achievements but endanger society. Participants viewed their use outside war zones as both illegal and morally indefensible, expressing concerns over the dehumanisation inherent in remote targeting. They argued that engaging with suspected terrorists without judicial oversight might violate due process. Hence, they stressed the importance of more nuanced national and international regulatory mechanisms.